2003
DOI: 10.1034/j.1600-0609.2003.00131.x
|View full text |Cite
|
Sign up to set email alerts
|

Core binding factor (CBF) acute myeloid leukemia: is molecular monitoring by RT–PCR useful clinically?

Abstract: Clonal chromosomal abnormalities are the most important prognostic indicators in acute myeloid leukemia (AML). Two of the most prevalent cytogenetic subtypes of adult primary AML, t(8;21)(q22;q22) and inv(16)(p13q22)/t(16;16)(p13;q22), are characterized by disruption of the AML1(CBFA2, RUNX1) and CBFbeta genes, respectively, which encode subunits of core binding factor (CBF), a regulator of normal hematopoiesis. At the molecular level, t(8;21) and inv(16)/t(16;16) result in the creation of novel fusion genes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 66 publications
(116 reference statements)
0
8
0
Order By: Relevance
“…11,12,30,33,34 The presence of MRD has been associated with an increased risk of relapse in most clinical studies. [6][7][8][9][10][11][12][13][14][15][16][17][18] In our series we demonstrated that both FC and RQ-PCR may provide complementary information in the MRD follow-up of t (8,21) and inv(16) AML patients. Previous studies using multiparametric FC have shown the prognostic value of MRD identification after AML treatment.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…11,12,30,33,34 The presence of MRD has been associated with an increased risk of relapse in most clinical studies. [6][7][8][9][10][11][12][13][14][15][16][17][18] In our series we demonstrated that both FC and RQ-PCR may provide complementary information in the MRD follow-up of t (8,21) and inv(16) AML patients. Previous studies using multiparametric FC have shown the prognostic value of MRD identification after AML treatment.…”
Section: Discussionmentioning
confidence: 90%
“…Monitoring MRD by molecular or immunophenotypic methods seem to be of interest to define those patients with a high risk of relapse. [6][7][8][9][10][11][12][13][14][15][16][17][18] Molecular techniques based on the detection of gene-fusion products are restricted to AML with specific chromosomal rearrangements, whereas multiparametric flow cytometry (FC) may be applied to more than 80% of AML cases. Accordingly, MRD in AML with t(8;21) and inv(16) AML may be analyzed using both methods.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the presence of unique transcripts, CBF AML is amenable to molecular monitoring of disease. 15-17 Multiple log reductions in fusion transcripts after induction and consolidation therapies are associated with better EFS. 16 Interventions designed to be implemented at times of molecular progression of disease or lack of optimal molecular response may improve outcome in patients with CBF AML, including secondary CBF AML.…”
Section: Discussionmentioning
confidence: 99%
“…The translocation (8;21)(q22;q22) and inversion or translocation of chromosome 16, which are commonly found in de novo AML, are associated with disruption of the core binding factor (CBF) transcription factor. These abnormalities define the CBF AML subtype, which is associated with the most favorable risk, including response to therapy (55). A Cancer and Leukemia Group B trial found higher overall survival with high-versus low-dose cytarabine therapy in CBF AML; complete response rates were about 90%, and overall survival was Ͼ50% at 5 years in these patients (56).…”
Section: Case Study: Treatment Of Aml With Cytarabine/topo II Inhibitmentioning
confidence: 99%